A conceptual framework for achieving good governance at open and distance learning institutions. (2nd January 2017) - Khanna, Pankaj
Abstract: This paper describes a good governance architecture framework that would bring significant improvements in the overall working of open and distance learning institutions in a well-structured and systematic way. The good governance framework is articulated with seven basic principles which are performance, transparency, accountability, participation, leadership, consensus orientation and fairness. These principles are structured with the good governance practices which relate to performing well for the assigned goals and objectives, promoting values for the organisation, making well-informed and transparent decisions, focusing on the organisation's purpose and outcomes, capacity building and managing risks effectively. These principles and suggested practices in the framework would become tools for developing an improvement strategy so as to help in the smooth operation and efficient management of the institution concerned. The developed system would bring about significant improvement in the teaching–learning activity as well as in the quality of distance education. It would also enhance the efficiency, effectiveness and overall performance of the institutional management which is crucial to the continuous development of the institution concerned. Thus, the proposed good governance framework when implemented in an open and distance education institution would improve the quality of distance education and also increase its accessibility in a well-organised and structured way.